Association between a Variant in MicroRNA-646 and the Susceptibility to Hepatocellular Carcinoma in a Large-Scale Population - Rui Wang; Jun Zhang; Weiru Jiang; Yanyun Ma; Wenshuai Li; Bohan Jin; Heping Hu; Jiucun Wang; Yi Liu; Jie Liu (The Scientific World Journal)
Background. Single-nucleotide polymorphisms in microRNAs play important roles in oncogenesis and cancer development. Objective. We aim to explore whether miR-646 rs6513497 is associated with the risk of hepatocellular carcinoma. Methods. Total 997 HCC patients and 993 cancer-free controls were enrolled in this study. Genotyping was performed using MassARRAY method. Results. Compared with the T allele of rs6513497, the G allele was associated with a significantly decreased risk of HCC (OR = 0.788, 95% CI = 0.631–0.985, P = 0.037); moreover, a more protective effect of the G allele was shown in males (OR = 0.695, 95% CI = 0.539–0.897, P = 0.005 in HCC and OR = 0.739, 95% CI = 0.562–0.972, P = 0.030 in HBV-related HCC), basically in a dominant manner (HCC: OR = 0.681, 95% CI = 0.162–0.896, P = 0.006; HBV-related HCC: OR = 0.715, 95% CI = 0.532–0.962, P = 0.027). Conclusions. Our findings support the view that the miR-646 SNP rs6513497 may contribute to the susceptibility of HCC.